2017
DOI: 10.1155/2017/9264914
|View full text |Cite
|
Sign up to set email alerts
|

Recuperating Lung Decoction Attenuates the Oxidative Stress State of Chronic Obstructive Pulmonary Disease by Inhibiting the MAPK/AP‐1 Signal Pathway and Regulating γ‐GCS

Abstract: Purpose/Objective. To evaluate the effects of Recuperating Lung Decoction (RLD) on the indices of oxidative stress in a rat model of COPD and detect the indices of the MAPK/AP-1/γ-GCS signal pathway for a further survey of the possible targeting site of RLD. Methods/Materials. The rats of COPD were treated with RLD. The protein levels of glutathione (GSH), oxidized glutathione (GSSG), 8-hydroxy-2-deoxyguanosine (8-OHdG), and 4-hydroxynonenal (4-HNE) were measured. In addition, the levels of key signaling molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…On the one hand, it can activate downstream target gene c-Jun to help cells cope with a variety of stimuli, such as cytokines, bacteria, and diseases. 19 On the other hand, p38 can enhance the activity of transcription factors c-fos and c-jun, participate in the expression of apoptosis-promoting proteins such as TNF-a, and regulate the inflammatory process. The results showed that the expression of JNK and p-JNK in group H was lower than that in group N, which indicated that penehyclidine hydrochloride could inhibit the JNK/MAPK pathway in mechanically ventilated rats with COPD, improve the inflammatory response mediated by the JNK/MAPK pathway, improve the inflammatory edema of lung tissue caused by neutrophil activation and aggregation in airway mucosa, and improve airflow restriction, all of which would protect the lung function of the rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, it can activate downstream target gene c-Jun to help cells cope with a variety of stimuli, such as cytokines, bacteria, and diseases. 19 On the other hand, p38 can enhance the activity of transcription factors c-fos and c-jun, participate in the expression of apoptosis-promoting proteins such as TNF-a, and regulate the inflammatory process. The results showed that the expression of JNK and p-JNK in group H was lower than that in group N, which indicated that penehyclidine hydrochloride could inhibit the JNK/MAPK pathway in mechanically ventilated rats with COPD, improve the inflammatory response mediated by the JNK/MAPK pathway, improve the inflammatory edema of lung tissue caused by neutrophil activation and aggregation in airway mucosa, and improve airflow restriction, all of which would protect the lung function of the rats.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it can activate downstream target gene c-Jun to help cells cope with a variety of stimuli, such as cytokines, bacteria, and diseases. 19 On the other hand, p38 can enhance the activity of transcription factors c-fos and c-jun, participate…”
Section: Dovepressmentioning
confidence: 99%
“…For example, Recuperating Lung Decoction could inhibit the MAPK/AP-1 signaling pathway to downregulate oxidative stress, resulting in the improvement of antioxidation of COPD. [ 32 ] Indeed, apoptosis was the second most indicated pathway in KEGG analysis. Whether in p53 signaling way, Kaposi sarcoma-associated herpesvirus infection pathway, or human immunodeficiency virus 1 infection pathway, the genes were primarily involved in apoptosis pathway ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 family plays essential roles in cell proliferation and survival 28 , which critically involves in MAP kinases pathways in various cellular types 29 31 . Previous data revealed that the extracellular signal-regulated kinases (ERK) and the c-Jun NH2-terminal kinases (JNK), two essential members of MAP kinases, can be activated in VSMCs from the acutely induced hypertensive rats, with the up-regulated gene expression of c-Fos and c-Jun , as well as the enhanced AP-1 DNA-binding activity 32 .…”
Section: Discussionmentioning
confidence: 99%